Protocol for the SACLA trial: Efficacy and safety of subretinal monteplase for submacular hemorrhage in a phase II single-arm multicenter decentralized clinical trial - Noriko Yoshida; Yuko Kobayakawa; Kouta Funakoshi; Sakiko Kimura; Kazuhisa Hosoya; Yuya Shinkawa; Takuma Furukawa; Tsubasa Mitsutake; Toshimi Hoshiko; Ayako Takamori; Naoto Kawahara; Hiroto Terasaki; et al. (PLoS ONE, 2026)
Submacular hemorrhage (SMH), which may arise from age-related macular degeneration, retinal arterial macroaneurysm, and other causes, can result in severe vision loss and central visual field impairment. Although tissue plasminogen activator (tPA) is used off-label to treat SMH in many countries, no formulation has been approved for this indication. Because early intervention is critical when tPA is used for SMH, limited access to centers that can provide this treatment may delay care and reduce treatment opportunities. Decentralized clinical trials (DCTs) reduce or eliminate the need for participants to travel to trial sites. We therefore designed the investigator-initiated SACLA trial to evaluate subretinal tPA for SMH. The DCT framework is intended to reduce logistical barriers related to the disease severity and rarity. The SACLA trial is a phase II multicenter, open-label, single-arm surgical study with a pre-post comparison design (jRCT2071250003). Twenty eligible participants will undergo pars plana vitrectomy followed by subretinal injection of 0.1 mL (8,000 IU) of tPA. Participants will remain hospitalized at the trial site until the primary outcome, change in central foveal thickness (CFT) from baseline at Week 1, is assessed. Thereafter, follow-up visits will be conducted at either the trial site or partner sites within the DCT framework. Secondary efficacy outcomes include change in CFT from baseline, presence of a foveal hemorrhage measuring at least 1 disc diameter, best-corrected visual acuity (BCVA), and change in BCVA from baseline at Weeks 4 and 12. Adverse events will be collected throughout the 12-week observation period to assess safety. The protocol and related study documents were reviewed and approved by the Saga University Hospital Institutional Review Board. This study is designed to generate prospective evidence on the feasibility, short-term anatomical response, and safety of subretinal tPA for SMH.